(untitled) (Praxis Educativa, 2025)
This article proposes a decolonial methodology for teaching social sciences in Latin America, grounded in critical Latin American perspectives. The Walking the Decolonial Teaching proposal is presented as an insubordinate and insurgent approach that seeks to transform hegemonic educational practices. The text analyzes the theoretical foundations of decoloniality, critical interculturality, and intersectionality, and their application in education. A didactic sequence is proposed, including learning actions such as naming, making visible, understanding, imagining, and creating, aimed at developing critical and decolonial awareness in students. The article concludes by reflecting on the challenges and possibilities of implementing decolonial pedagogies in the Latin American context.